PENERAPAN STRATEGI THINK TALK WRITE DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.3 SMPN 21 PEKANBARU - Nanik Mulyani; Yenita Roza; Jalinus Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The background of this research is some students do not reach minimum mastery criteria yet and learning process is not accordance with the regulation of the minister of national education. This research aims to improve learning process and mathematics learning outcomes in SMPN 21 Pekanbaru by implementing Think Talk Write strategy in cooperative learning model. Subject in this research were students in class VII.3 who have heterogeneous academic ability. This research is a classroom action research with two cycles. Each cycle has four stages, the stages are planning, action, observation and reflection. The result of this research showed that the teacher and students activities have done well after given the action. An increase in the number of students who achieved the minimum mastery criteria of first cycle (47,5%) and second cycle (57,5%) compared to the number of students who achieve the minimum mastery criteria on base score (17,5%). Results of this research indicate that the application of Think Talk Write strategy in cooperative learning model can improve learning process and the mathematics learning outcomes of students grade VII.3 SMPN 21 Pekanbaru in the first semester academic year 2013/2014.Key words: Learning process, Mathematics learning outcome, Cooperative learning, Think Talk Write Strategy, Classroom action research